A108 USTEKINUMAB IS EFFECTIVE FOR INDUCING CLINICAL, ENDOSCOPIC, AND RADIOGRAPHIC RESPONSE IN REFRACTORY MODERATE-TO-SEVERE CROHN'S DISEASE: A MULTICENTRE COHORT STUDY. (1st March 2018) - Ma, C; Fedorak, R; Kaplan, G G; Dieleman, L A; Devlin, S; Stern, N; Kroeker, K I; Seow, C; Leung, Y; Novak, K L; Halloran, B P; Huang, V; et al.
Abstract: Background: Ustekinumab is a monoclonal antibody targeting the p40 subunit of interleukins 12 and 23. Gastroenterologists have begun to prescribe ustekinumab off-label for treatment of Crohn's disease (CD) due to promising clinical trials but robust open label data is lacking Aims: Assess the real-world efficacy of ustekinumab for inducing clinical, endoscopic, and radiographic response in CD Methods: A retrospective multicentre cohort study was performed at two academic institutions (University of Calgary, University of Alberta) on CD patients receiving ustekinumab between 2011–2016. The primary outcome was achievement of clinical or objective response at 3, 6, and 12 months after induction. Clinical response was defined by symptom improvement and reduction in Harvey Bradshaw Index of >2 points with tapering off corticosteroids. Objective response was defined by improvement in endoscopic or radiographic CD, as assessed by ileocolonoscopy, contrast-enhanced ultrasound, or CT/MR enterography Results: We identified 167 CD patients treated with ustekinumab. Median follow-up was 39.0 weeks (IQR 23.3–87.1 weeks). 95.2% (159/167) had previously failed anti-TNF therapy. 63 patients (37.7%) had clinical response at 3 months. Among 143 patients followed for 6 months or discontinuing drug prior to 6 months, clinical response was achieved in 57.0% (85/149). At 12 months, clinical response was achieved in 54.2% (58/107) of patients. Endoscopic or radiographic response was demonstrated in 48.6% of patients (54/111) at 6 months and 46.9% of patients at 12 months (38/81). Fifty-three patients (31.1%) experienced an adverse event: 8 patients discontinued therapy due to intolerable side effects (4.8%) Conclusions: To the best of our knowledge, this multicentre cohort study is the largest reported open label experience with ustekinumab for CD. We found that ustekinumab was a safe and effective therapy for inducing steroid-free clinical and objective endoscopic and radiographic response Funding Agencies: CAG